1994
DOI: 10.1161/01.hyp.23.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in salt-sensitive patients. A marker for renal and cardiovascular risk factors.

Abstract: We previously showed that a high salt diet increases glomerular capillary pressure in salt-sensitive hypertensive patients and suggested that this may underlie the greater propensity of these patients to develop renal failure. Because microalbuminuria is considered an initial sign of renal damage, we have tested whether salt-sensitive patients display greater urinary albumin excretion than salt-resistant hypertensive patients. Twenty-two patients were placed on a low sodium intake (20 mEq/d) for 7 days followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
133
0
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(161 citation statements)
references
References 50 publications
(22 reference statements)
16
133
0
6
Order By: Relevance
“…These studies have also confirmed that saltsensitive hypertensive individuals manifest greater urine albumin excretion rate than salt-resistant patients. 18 Moreover, while office blood pressure was not different among these two groups, daytime and nighttime ambulatory blood pressure levels were significantly greater among salt-sensitive than among salt-resistant individuals. Finally, salt-sensitive individuals manifested a greater rise in blood pressure during exercise than salt-resistant individuals and a greater frequency of silent myocardial ischemia than salt-resistant individuals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These studies have also confirmed that saltsensitive hypertensive individuals manifest greater urine albumin excretion rate than salt-resistant patients. 18 Moreover, while office blood pressure was not different among these two groups, daytime and nighttime ambulatory blood pressure levels were significantly greater among salt-sensitive than among salt-resistant individuals. Finally, salt-sensitive individuals manifested a greater rise in blood pressure during exercise than salt-resistant individuals and a greater frequency of silent myocardial ischemia than salt-resistant individuals.…”
Section: Discussionmentioning
confidence: 80%
“…[18][19][20] Thus, a close relation may exist between salt sensitivity, microalbuminuria and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…However, Na þ sensitivity has been linked to a number of metabolic and physiologic abnormalities such as albumin excretion, 16,17 left ventricular hypertrophy 18,19 and dyslipidaemia. 20 In a crosssectional study in Japanese hypertensives, cardiovascular events were found to be twice as common among Na þ sensitive hypertensives as among Na þ resistant hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that salt-sensitive hypertensive patients exhibit excess prevalence or severity of left ventricular diastolic dysfunction 17 and hypertrophy 18 (perhaps linked to decreased nocturnal 'dipping' of BP 19 ) and increased incidence of stroke 20 and severity of microalbuminuria. 21 This end-organ damage pattern resembles that of saltsensitive hypertensive rats, such as DOC-salt and Dahl-salt-sensitive (SS). Most recently, Weinberger and co-workers have provided evidence that salt-sensitivity of BP of normotensive individuals carries with it the same detrimental long-term prognosis (mortality) as hypertension in salt-resistant patients.…”
Section: Introductionmentioning
confidence: 89%